Pengaruh DPK, CAR dan BOPO terhadap ROA Bank Panin Dubai Syariah Periode 2020-2024 - Pauzi, Irpan; Jalaludin, Jalaludin; Damiri, Ahmad (STIES INDONESIA PURWAKARTA Dan MES PURWAKARTA, 2025)
Panin Dubai Syariah Bank's performance for the 2020–2024 period shows complex dynamics in the management of Third Party Funds (DPK), capital (CAR), operational efficiency (BOPO), and profitability (ROA). Fluctuations in TFD over several years reflect changes in customer confidence and funding strategies, while the CAR ratio experienced pressure at the beginning of the period but improved until 2024. On the other hand, the BOPO ratio tended to increase, indicating challenges in operational efficiency, although it improved in 2021–2022. This study aims to analyze the effect of DPK, CAR, and BOPO on ROA both partially and simultaneously. The research method uses a descriptive quantitative approach with secondary data obtained through documentation studies from Panin Dubai Syariah Bank's official reports, OJK publications, and related academic literature. The results show that DPK has a significant effect on ROA (t-value of 2.213 > t-table 2.17881) with a contribution of 15.7%, supporting Komariah's findings. CAR does not have a significant effect on ROA (t-count of 0.823 < t-table 2.17881), in line with the view that a high capital ratio does not always reflect the efficiency of productive assets. Conversely, BOPO has a very significant effect on ROA (t-value > t-table of 34.153 > 2.17881) with a contribution of 99.8%, confirming that operational efficiency is a dominant factor in determining bank profitability. Simultaneously, the three variables have a significant effect on ROA (Fcount of 581.555 > Ftable 3.259) with a combined contribution of 99.3%, supporting Amanda Rachmawati's research. These findings emphasize the importance of managing operational efficiency and funding strategies in increasing the profitability of Islamic banks. The impact of this study has practical implications for Islamic banking management to strengthen fund raising strategies, maintain capital quality, and improve operational efficiency as a sustainable effort to strengthen the competitiveness and reputation of institutions in the Islamic financial industry.